PROPERTIES OF SEQUENCES RELATED TO BALANCING NUMBERS - S. J. Gajjar (ShodhKosh: Journal of Visual and Performing Arts, 2023)
In this paper, we discuss a new approach to find the sequence of Balancing Numbers. We discuss some properties of two special sequences un and vn related to the sequence of Balancing Numbers. W investigate the relations of these sequences with the sequence of Balancing Numbers. Also we give some new identities of Balancing Numbers.